“De-emplotting” History: Genre, Violence and Subversion in Christopher Marlowe’s "Edward II" - Gualberto Valverde, Rebeca (Complutense Journal of English Studies, 2017)
Taking into consideration Hayden White’s seminal argument about historical emplotment, and relating such notion to traditional explanations about the ritualistic structure of Tudor historiography, this article reassesses Chistopher Marlowe’s Edward II (ca. 1592) from the perspective of genre in order to expose how the play counter-effects the dominant ideology of the Tudor regime concerning royal authority. The encodation of historical events into the icon of romance, and the dramatic superimposition of tragic conventions upon such an iconic structure arguably confront two opposing modes of representing violence onstage, which determines a theatrical interplay of power discourses that arguably dramatizes the desacralization of kingship through the immanent representation of its sacredness. As this article argues, these dialectics articulates the political anxieties of Renaissance England from within generic categories, and it effectively subverts the well-established strategies of legitimization that idealized (and rewrote) violence, history and monarchy in Tudor England.